1. for any sets X and Y, we define the symmetric difference X ∆Y by:

X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y)
Prove the following:
-for all sets A,B and C, if A - (B ∩ C) = ∅ then A- C ⊆ B
- for all sets A,B and C, if A ⊆ B ∪ C and B ⊆ C ∪ A then A∆B ⊆ C
- for all sets A,B and C, if A∆B = A∆C then B ⊆C

Similar Questions
  1. 1. for any sets X and Y, we define the symmetric difference X ∆Y by:X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove
    1. answers icon 0 answers
  2. 1. for any sets X and Y, we define the symmetric difference X ∆Y by:X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove
    1. answers icon 0 answers
  3. 1. for any sets X and Y, we define the symmetric difference X ∆Y by:X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove
    1. answers icon 0 answers
  4. 1. for any sets X and Y, we define the symmetric difference X ∆Y by:X∆Y = (X - Y) ∪ (Y - X) = (X ∪ Y) - (X ∩ Y) Prove
    1. answers icon 0 answers
more similar questions